2005
DOI: 10.1021/ma048273s
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Single-Walled Carbon Nanotubes with Well-Defined Polymers by Radical Coupling

Abstract: Polystyrene and poly[(tert-butyl acrylate)-b-styrene] with well-defined molecular weights and polydispersities were prepared by nitroxide-mediated free-radical polymerization. The homopolymers and block copolymers were used to functionalize shortened single-walled carbon nanotubes (SWNTs) through a radical coupling reaction involving polymer-centered radicals generated at 125 °C via loss of the stable free-radical nitroxide capping agent. The resulting polymer−SWNT composites were fully characterized and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(185 citation statements)
references
References 41 publications
5
177
1
1
Order By: Relevance
“…1450, 1700 and 1900 nm remain similar following both the ion exchange or p-p stacking processes, suggesting the one-dimensional p-conjugation electronic states of fluorescent SWNTs complexes are preserved. [14,31,[66][67][68][69] This observation contrasts with a previous report, in which pyrene-functionalized SWNTs were prepared via sidewall cycloaddition and the absorption peak of the first band gap disappeared completely, indicating a deterioration of the one-dimensional electronic states. [70] Additional evidence for the retention of the onedimensional electronic states of SWNTs comes from Raman spectra.…”
Section: Resultscontrasting
confidence: 88%
“…1450, 1700 and 1900 nm remain similar following both the ion exchange or p-p stacking processes, suggesting the one-dimensional p-conjugation electronic states of fluorescent SWNTs complexes are preserved. [14,31,[66][67][68][69] This observation contrasts with a previous report, in which pyrene-functionalized SWNTs were prepared via sidewall cycloaddition and the absorption peak of the first band gap disappeared completely, indicating a deterioration of the one-dimensional electronic states. [70] Additional evidence for the retention of the onedimensional electronic states of SWNTs comes from Raman spectra.…”
Section: Resultscontrasting
confidence: 88%
“…[36][37][38] It was first fabricated by the in situ polymerization process. Various research groups have reached the same results: that the initiator fragment is first attached to the double bond and the polymer chain is propagated from the surface of CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability of nanocomposites is determined by competitive effects. Whereas MWCNTs act as radical scavengers at low loadings [14] delaying the degradation pattern and enhancing thermal stability, it has also been reported that the enhancement in thermal conductivity on MWCNT addition to the matrix lowers the degradation temperatures [32]. The thermal stability of the nanocomposites depends to a certain extent on the interaction between the phases [33] (which can be presumed to be good here at least from the matrix perspective as PPE/PS is miscible) and the amount of residual metal catalyst in the MWCNTs which was used for their production.…”
Section: Characterization Of the Compositesmentioning
confidence: 99%